Effects of Oral Vitamin C Supplementation on Liver Health and Associated Parameters in Patients With Non-Alcoholic Fatty Liver Disease: A Randomized Clinical Trial - He, Zhangya; Li, Xiaomin; Yang, Hexiang; Wu, Pei; Wang, Shanshan; Cao, Dan; Guo, Xiaoxiao; Xu, Zhangrui; Gao, Jiayi; Zhang, Wanyu; Luo, Xiaoqin (Frontiers in Nutrition, 2021)
Background: Non-alcoholic fatty liver disease (NAFLD) is now recognized as the most prevalent hepatic disorder worldwide, and an unhealthy lifestyle is the leading risk factor for its occurrence. Vitamin C (VC) has been suggested to protect NAFLD, whereas evidence from randomized controlled trials is sparse. Objectives: Here, we aimed to investigate the potential benefits of VC supplementation daily on liver health and associated parameters in patients with NAFLD. Methods: In this double-blind, randomized controlled trial (RCT), 84 NAFLD patients aged 18-60 years old were assigned to 12 weeks of oral treatment with either Low (250 mg/d, n=26), Medium (1000 mg/d, n=30) or High (2000 mg/d, n=28) dose of VC supplements. Results: After intervention, the Medium group had a more significant decrease in aspartate aminotransferase (AST) [Medium, -5.00 (-10.25, -1.75) vs. High, -2.50 (-7.75, 0.00), P=0.02] and alanine aminotransferase (ALT) [Medium, -8.00 (-18.00, -1.75) vs. High, -3.50 (-13.75, 4.25), P=0.05; Medium vs. Low, -3.00 (-9.00, 5.50), P=0.031]. The levels of other indicators of liver health, such as gamma-glutamyl transferase (γ GT), alkaline phosphatase (ALP), total bilirubin (TBIL) and direct bilirubin (DBIL) were decreased after the intervention but comparable among the three groups, and so did the parameters of glucose metabolism, such as fasting insulin, fasting glucose and homeostasis model assessment for insulin resistance (HOMA-IR). The plasma level of VC in patients as well as total adiponectin and HMW adiponectin levels were also elevated but not in a dose-dependent manner. Meanwhile, analysis of fecal microbiota composition showed an increase of the Alpha diversity (ACE, shannon, chao1, and simpson) both in the Low and Medium groups. Conclusion: 12 weeks of VC supplementation, especially 1000 mg/d, improved liver health and glucose metabolism in patients with NAFLD. The elevated plasma levels of VC, total and HMW adiponectin, and the improvement of intestinal microbiota may have made some contributions.